Food insecurity: What can the world trading system do about it? - Wolff, Alan Wm.; Glauber, Joseph W. (Peterson Institute for International Economics, 2023)
Russia’s invasion of Ukraine, a major supplier of grain to the Middle East and Africa, has triggered deep concerns over access to affordable food across the globe. The alarming rise in food insecurity across the world due to conflicts makes it increasingly urgent to set ground rules for sharing food in global markets and getting food to places most in need to avoid starvation and famine. The most glaring and relevant gap in the rules of the world trading system pertains to sharing food in times of scarcity. The authors recommend using the World Trade Organization’s (WTO) long-standing accords on agriculture as a basis to provide guidelines for supplying food to global markets, especially areas in need. The most obvious shortcoming in the rules is that WTO members are largely free to restrict exports of food. The WTO rules need to be updated to take into account climate change, extreme weather, military conflicts, pandemics, and other factors that interfere with food production. The WTO can specify factors that an exporting country must take into account when imposing an export restriction on food, and it can require consultations to deal with severe disruptions in world food trade. It can also serve to mediate the interests of food exporters and importers in enhancing food security.